2022
DOI: 10.1093/cercor/bhab499
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation of others during action observation in posterior medial prefrontal cortex

Abstract: Making decisions based on the actions of others is critical to daily interpersonal interactions. We investigated the representations of other’s actions at single neural level in posterior medial prefrontal cortex (pmPFC) in two monkeys during the observation of actions of another agent, in a social interaction task. Each monkey separately interacted with a human partner. The monkey and the human alternated turns as actor and observer. The actor was required to reach one of two visual targets, avoiding the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The near-perfect performance of the monkeys after both the Good and Bad agents’ turns confirms the monkeys’ ability to effectively remember the last choice made by the human agent during the observer role. Thus, while the early anti-correlated beta-gamma activity can be considered a neural correlate of the anticipated target choice during the delay period, as shown in our previous studies, 14 , 15 the opposite beta-gamma modulation, which lasts longer during partner reaching, may still reflect memory of the partner choice. 50 The observation that the beta band encoded information about the target chosen by the human partner during the beginning of the subsequent trial provides further support for this hypothesis.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…The near-perfect performance of the monkeys after both the Good and Bad agents’ turns confirms the monkeys’ ability to effectively remember the last choice made by the human agent during the observer role. Thus, while the early anti-correlated beta-gamma activity can be considered a neural correlate of the anticipated target choice during the delay period, as shown in our previous studies, 14 , 15 the opposite beta-gamma modulation, which lasts longer during partner reaching, may still reflect memory of the partner choice. 50 The observation that the beta band encoded information about the target chosen by the human partner during the beginning of the subsequent trial provides further support for this hypothesis.…”
Section: Discussionsupporting
confidence: 49%
“…In our previous work, during the Nonmatch-to-goal task, mPFC single neurons showed a robust activation both when monkeys performed the task and observed a human agent performing the task. 14 , 15 Here, for all the artifact-free channels, we checked whether the voltage at targets presentation differed between the two conditions in which the monkey was the Actor and the Observer. Each channel was considered visually selective if its voltage was modulated by > 2SD from baseline for 50 ms immediately after the targets were presented (see STAR Methods ; Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such persistent activity has also been observed in relation to several other cognitive processes in addition to short-term memory 13 . However, further evidence has challenged this view by demonstrating a more dynamic coding than previously thought 23,24,28,29,71 . More recent studies have also shown that these coding schemes are not even mutually exclusive in a given brain area, but rather that they can coexist 48 and be associated with distinct neuronal populations [50][51][52] , undermining the idea of rigid categorical separation and laying the foundations for conceiving mixed and heterogeneous representations in the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 92%